Population Health Management: Foundations, Organizational Readiness, and Implementation Approaches: A Narrative Review - Mohammad AlJabr; Assim AlAbdulKader; Ahmed Alabdrabalnabi; Lama Al-Mazroa; Leyan Alotaibi; Saad F. Alshahrani; Saad Alshahrani (Population Health Management, 2026)
Population health management (PHM) has emerged as a central strategy for improving outcomes, reducing avoidable utilization and strengthening system-level performance; however, it remains inconsistently defined and frequently conflated with public health, analytics, or high-performing primary care. This narrative review synthesizes multidisciplinary literature to clarify PHM definitions, compare operational frameworks, identify foundational organizational requirements, and propose a phased implementation pathway grounded in organizational maturity. Searches across major databases identified 42 peer-reviewed articles and authoritative reports published between 2000 and 2024 that addressed PHM conceptual foundations, frameworks, enabling conditions, and implementation strategies. Across diverse models—including accountable care organizations, integrated delivery systems, and national PHM initiatives—common structural components consistently emerged: population attribution and segmentation, targeted intervention design, interoperable data infrastructure, governance alignment, workforce capability, financing integration, and continuous learning. Recurrent barriers included conceptual conflation, fragmented governance, misaligned incentives, and overreliance on analytics without corresponding care redesign. Organizational maturity—rather than analytic sophistication—appears to be the primary determinant of sustainable PHM performance. The evidence suggests that PHM succeeds when conceptual clarity, governance structures, workforce capability, interoperable data systems, and financing alignment coevolve within a deliberate, phased transformation process. Treating PHM as a technical enhancement or isolated program undermines scalability and durability. A maturity-oriented approach provides a practical roadmap for health systems seeking to advance from fragmented initiatives toward sustained population accountability.